2010
DOI: 10.2474/trol.5.80
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trace Water and Oxygen in a Hydrogen Environment on Pure Fe Friction and Wear

Abstract: The influence of trace water and oxygen in a hydrogen environment on the sliding behavior of pure iron was studied using a newly developed pin-on-disk apparatus in a vacuum chamber equipped with an advanced gas replacement system. The hydrogen environment in the siding tests contained 0.5 to 95 ppm water and 0.07 to 2 ppm oxygen; a turbo-molecular pump was used for evacuation and a chemical filter for reducing water and oxygen in the hydrogen gas supplied to the chamber. The concentrations of water and oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 12 publications
3
16
3
Order By: Relevance
“…The relationship between concentrations of water and oxygen in hydrogen environments for this study is shown in Fig.3 in comparison with that for the previous study [5]. It is confirmed that all of oxygen concentrations for this study were within 6.5 ppb regardless of a water concentration which ranged between 2 and 8,500 ppb.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The relationship between concentrations of water and oxygen in hydrogen environments for this study is shown in Fig.3 in comparison with that for the previous study [5]. It is confirmed that all of oxygen concentrations for this study were within 6.5 ppb regardless of a water concentration which ranged between 2 and 8,500 ppb.…”
Section: Resultssupporting
confidence: 84%
“…After confirming that concentrations of water and oxygen in the gas were stabilized at the targeted values, a sliding test was started. Table 2 shows experimental conditions and these conditions are same as ones used in our previous studies [1,4,5,8]. To know the influences of atmospheric gases, moderate values for a load and sliding speed were selected.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations